The politics of oil in Venezuela - Tugwell, Franklin (Stanford, Calif. : Stanford University Press, 1975)
This volume examines the politics of oil in Venezuela. This include the political settings, the various administrations (Betancourt, Leoni, Caldera).
Includes index.
Includes bibliographical references: p. 197-204.
lje 23/01/2019
Loans
Keywords: Petroleum industry and trade; Oil and gas; Venezuela